PENGUJIAN PERAN PERLINDUNGAN INVESTOR DAN KULTUR TERHADAP PERILAKU MANAJEMEN LABA PADA PERUSAHAAN KELUARGA: STUDI INTERNASIONAL - Francisca Reni Retno Anggraini; Yavida Nurim; Nung Harjanto (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This study aims to examine the role of investor protection level, culture, and family ownership level variables to the family firms’ earnings quality. This study is based on two opposite arguments about the effect of family ownership in family firms. This study uese LaPorta et al.’s proxy to measure investor protection level, and then the are two culture; power distance and individualism/collectivism. The family ownership is proxied by the percentage of share owned by individual or family, et least 20%. The sample is taken from 2002-2008 OSIRIS data base. Based on the examination of family firms in around 17 countries, this study reveals that the individual or family as insider shareholders has positive effect to the earnings quality. Surprisingly, investor protection has less benefit in increasing the family firms’ earnings quality, but culture in a country influences the family’s behaviour through ameliorating or deteriorating the earnings quality. Key words: Investor protection, culture, family firm, and earnings quality